Sesontengan Sebagai Representasi Budaya dan Religius Dalam Upacara Yadnya di Desa Banyuatis - Gede Mahardika (Jurnal Penelitian Agama Hindu, 2026)
This research is motivated by the dynamics of ritual language use in the implementation of yadnya ceremonies in Bali, particularly in Banyuatis Village, amid the limited mastery of Sanskrit and Kawi mantras and the influence of modernization. In practice, the community continues to require a medium of religious communication capable of bridging theological understanding with the everyday experiences of devotees. Sesontengan, as a form of prayer in the Balinese language, emerges as a cultural and religious expression that lives within the community’s oral tradition. This study aims to analyze the role of sesontengan as a cultural and religious representation in yadnya ceremonies, examine its function as an alternative substitute for puja mantras, and explore its contribution to preserving Balinese Hindu identity. The method used is a descriptive qualitative approach with a perspective of the anthropology of religion. Data were collected through in-depth interviews, participatory observation, and documentation studies over a four-month period, involving temple priests (pemangku), banten makers, and traditional leaders as key informants. The findings indicate that sesontengan is not merely a ritual complement, but functions as a means of affirming the meaning of yadnya, a medium of transcendental communication, and a vehicle for internalizing ethical and spiritual values based on Tri Hita Karana. Furthermore, sesontengan serves as an adaptive strategy in maintaining the continuity of religious practices amid social change, while also strengthening the use of the Balinese language as a marker of cultural identity. This study concludes that sesontengan is a dynamic and contextual ritual practice that plays an important role in preserving religious values, social solidarity, and the identity of Balinese Hinduism in the modern era.